ANALYSIS CONTROL SUPPLIES RAW MATERIALS WITH THE EOQ METHODS IN THE SMOOTHNESS OF THE PRODUCTION PROCESS - Muhammad Syarif Hidayatullah Elmas (Universitas Pendidikan Ganesha, 2017)
This study aims to know how the raw material inventory control zinc aluminum UD. Pribumi and to know the difference between the cost of inventory by UD. Pribumi and inventory costs of raw materials, according to calculations control analysis of raw materials. The data collection technique used was the study of literature and field research, whereas data analysis tools used determination of the Safety Stock, Order Quantity Calculation using Economic Order Quantity (EOQ), TIC and Maximum Inventory. From the analysis and discussion, the total cost of inventory for raw material zinc aluminum company spent on is Rp 13,326,326.2, - greater than using EOQ calculation of only Rp 6,538,820.19, - thereby save on inventory costs if the company is using EOQ method.